Gain enhancement of microstrip grid array antenna for 5G applications - Muhamad, W. A. W. (Institute of Electrical and Electronics Engineers Inc., 2016)
A single patch microstrip grid array antenna is presented. The proposed antenna is designed in rectangular diamond shape with dimension of 34 mm × 35 mm in width and length respectively. Rogers 5880 with a low relative permittivity of 2.2 is used as substrate with the thickness of 0.508 mm. The proposed microstrip grid array antenna successfully enhanced the antenna gain up to 11.32 dBi compared to existing silicon dioxide antenna, 2.99 dBi and 10.35 dBi for existing stacked patch antenna arrays. The reflection coefficient, S11 is -24.08 dB at frequency of 28 GHz. With ease of fabrication and low-profile, the proposed antenna is potentially be implemented in future 5G applications.